Studies in the history of the Greek text of the Apocalypse the ancient stems - Schmid, Josef 1893-1975; Hernández, Juan 1968- (Atlanta Society of Biblical Literature, 2018)
Cover -- Contents -- Acknowledgments -- Sigla and Abbreviations -- Translators' Introduction -- Foreword -- Introduction -- The Major Stems of the Greek Text of the Apocalypse and Their Interrelationships -- The Linguistic Style of the Apocalypse -- Appendix: Errata -- Bibliography -- Biblical References Index -- Modern Authors Index -- Subject Index